Analisis dan Perancangan Aplikasi Logistik dan Penerapan Metode Operasional Customer Relationship Management (Studi Kasus:Natur Salon & Spa) - Syafirafitri Anwar; Meliana Christianti J. (Maranatha University Press, 2019)
The purpose of this system development is to help a beauty salon to maintain their loyal customers and new customers do not choose other competitors with the promotion feature, help to keep a record of sales transactions and purchase transaction, help to do a point redeem of member, help to manage treatment and product data, provide purchase transaction report, and provide a reminder to restock the product which has reached the minimum amount. The application has two users which have a different role to access the application, where Owner role is able to do sales transaction, manage treatment data and sold product data, record purchase of a product, and manage automated promotion system, and cashier role is only able to do sales transaction.